Contemporary dialogue with the employer. Selected trends in the labour market - Monika Christoph (Uniwersytet Kazimierza Wielkiego, 2019)
The author of the article shows the emerging need to build an authentic dialogue and bilateral relationship between a modern employer and their employees. The basis and justified context for formulating such a statement is the analysis of dynamic changes in the sphere of human work and their professional biographies, the new dimension of which is clearly marked in the area of the modern environment of the organization. To confirm her considerations, the author of the article gives the results of the research presented in the Deloitte Global Human Capital Trends 2019 Report (N = 10,000, 2019), referring to changes and challenges organizations will face in the future, especially in relation to the staff. In summary, the topics of educational and professional aspirations of young people, academic counselling and the importance of education in preparing young people to occupy modern roles in the contract with the employer are also taken up.